Making Delhi inclusive, safe, resilient and sustainable (SDG-11) - Jain, A.K. (2015)
Delhi, the Capital of India, is facing several urban problems, such as shelter for the poor, environmental degradation, pollution, traffic congestion, shortages of infrastructure services, climate change, etc. The Government of India along with concerned State/UT, Governments has taken up the implementation of UN Sustainable Development Goals (SDGs) of which SDG 11 aims to make the cities inclusive, safe, resilient and sustainable by the year 2030. SDG 11 covers 10 targets including housing for all, sustainable urban transport, safeguarding cultural and natural heritage, disaster resilience and safety, reducing pollution, development of greenery and public spaces, mitigation and adaptation of climate change and development of sustainable, green buildings. In this pursuit it is necessary to adopt an approach which engages with the identity of the city while meeting the urban challenges. The article provides a basket of proposals, such as land reservation for social housing, emphasis on brown field development, walk to work, common utility ducts, pneumatic waste management, alternative and decentralized sanitation and sewage systems, vertical farming, geo-thermal cooling, etc., which can be the new frontiers of urban development. - Reproduced.
Keywords: Urban planning - India - Delhi; Urban planning